PROGRAM PEMBERDAYAAN MASYARAKAT DALAM PENANGANAN STUNTING DI KELURAHAN PANCUR, TAKTAKAN, SERANG BANTEN - Kosasih, Kosasih; Sujana, Nanan (Universitas Muhammadiyah Tangerang, 2023)
Stunting is one of the strategic problems experienced by people in Banten, especially in the Pancur sub-district, Serang, Banten. The socialization and training activity